What is the relationship between marketing of library sources and services and social media? A literature review paper. Issue 3 (29th January 2020) - Anwar, Muhammad; Zhiwei, Tang
Abstract : Purpose: The aim of this study is to determine the relationship between social media and libraries in terms of marketing. The present research is to find out the factors and impact as well as the issues related to libraries and marketing using social media. This study will give massive information regarding social media use for the marketing of library sources and services. Design/methodology/approach: This study so far has been taken into account to review all the related literature of social media and library marketing. All the related literature studies were reviewed according to the suggested objectives of the study. Findings: The present study reveals after reviewing literature that there is a great impact of social media on libraries. The literature shows that social media is the biggest change in the twenty-firstst century for library professionals and librarians. The reviewed literature studies have discovered that the libraries are facing too many challenges and issues to the adoption of social media for the marketing of library sources and services. The collected and analyzed works of the literature indicated that social media would be the best tool to promote library sources and services. Research limitations/implications: This research or study can serve the LIS professionals and librarians in the field of library and information science and librarianships that they are looking for the adoption and application of social media in the marketing of library sources and services to the targeted customers. Practical implications: This research or study can serve the LIS professionals and Librarians in the field of library and information science and librarianships that they are looking for the adoption and application of social media in the marketing of library sources and services to the targeted customers. Originality/value: To the best of the authors' knowledge, this study is one of the first among those researches that is to disclose the close relationship between social media and libraries in terms of marketing of library sources and services.